Acute Exposure to Crystalline Silica Reduces Macrophage Activation in Response to Bacterial Lipoproteins - Beamer, Gillian L.; Seaver, Benjamin P.; Jessop, Forrest; Shepherd, David M.; Beamer, Celine A. (Frontiers in Immunology, 2016)
Numerous studies have examined the relationship between alveolar macrophages (AMs) and crystalline silica (SiO2) using in vitro and in vivo immunotoxicity models; however, exactly how exposure to SiO2 alters the functionality of AM and the potential consequences for immunity to respiratory pathogens remains largely unknown. Because recognition and clearance of inhaled particulates and microbes are largely mediated by pattern recognition receptors (PRRs) on the surface of AM, we hypothesized that exposure to SiO2 limits the ability of AM to respond to bacterial challenge by altering PRR expression. Alveolar and bone marrow-derived macrophages downregulate TLR2 expression following acute SiO2 exposure (e.g., 4 h). Interestingly, these responses were dependent on interactions between SiO2 and the class A scavenger receptor CD204, but not MARCO. Furthermore, SiO2 exposure decreased uptake of fluorescently labeled Pam2CSK4 and Pam3CSK4, resulting in reduced secretion of IL-1β, but not IL-6. Collectively, our data suggest that SiO2 exposure alters AM phenotype, which in turn affects their ability to uptake and respond to bacterial lipoproteins.